STRATEGIC PLANNING OF INNOVATION GOAL-SETTING IN DEVELOPMENT OF URBAN AREAS - A. D. Murzin (Science and Innovation Center Publishing House, 2014)
This research focuses on the development of the goal setting concept in the strategic urban development and the identification of innovative priorities for sustainable development of urban areas, acting as catalysts for reforming of municipalities’ management. The purpose of this research is to establish an effective system of milestones of innovative development of urban areas in the process of strategic urban development. Methodological basis of the research is the complex of abstract and hypothetical and logical tools, as well as the axiomatic analysis of the problems and prospects of innovative development of urban areas. The research results include the study of terminological apparatus of urban innovations, formation of the main directions of innovation policy implementation in the process of urban development of urban areas, the development of a fundamental algorithm of strategic goal setting in the innovative development of urban areas. The scope of application of the research results is a system of planning of social and economic development of municipalities, as well as comprehensive programs of financing and investment support of social projects of the urban environment development. The main conclusion of this research is the statements of need for innovative orientation of plans for social and economic planning of the urban environment, revealing the negative effects of the inertial urban design, characteristic of most Russian cities, inattention to which can lead to a social and economic damage and even to a social, ecological and economic degradation of territories.